Identification and Verification of Quantitative Trait Loci Affecting Milling Yield of Rice - Hui Zhang; Yu-Jun Zhu; An-Dong Zhu; Ye-Yang Fan; Ting-Xu Huang; Jian-Fu Zhang; Hua-An Xie; Jie-Yun Zhuang (Agronomy, 2020)
Rice is generally consumed in the form of milled rice. The yield of total milled rice and head mill rice is affected by both the paddy rice yield and milling efficiency. In this study, three recombinant inbred line (RIL) populations and one F4:5 population derived from a residual heterozygous (RH) plant were used to determine quantitative trait loci (QTLs) affecting milling yield of rice. Seven traits were analyzed, including recovery of brown rice (BR), milled rice (MR) and head rice (HR); grain yield (GY); and the yield of brown rice (BRY), milled rice (MRY) and head rice (HRY). A total of 77 QTLs distributed on 35 regions was detected in the three RIL populations. Four regions, where qBR5, qBR7, qBR10, and qBR12 were located, were validated in the RH-derived F4:5 population. In the three RIL populations, all the 11 QTLs for GY detected were accompanied with QTLs for two or all the three milling yield traits. Not only the allele direction for milling yield traits was unchanged, but also the effects were consistent with GY. In the RH-derived F4:5 population, regions controlling GY also affected all three milling yield traits. Results indicated that variations of BRY and MRY were mainly ascribed to GY, but HRY was determined by both GY and HR. Results also showed that the regions covering GW5−Chalk5 and Wx loci had major effects on milling quality and milling yield of rice. These two regions, which have been known to affect multiple traits determining grain quality and yield of rice, provide good candidates for milled yield improvement.